One-Step Fabrication of Novel Polyethersulfone-Based Composite Electrospun Nanofiber Membranes for Food Industry Wastewater Treatment - Pervez, Md. Nahid; Talukder, Md Eman; Mishu, Monira Rahman; Buonerba, Antonio; Del Gaudio, Pasquale; Stylios, George K; Hasan, Shadi W.; Zhao, Yaping; Cai, Yingjie; Figoli, Alberto; Zarra, Tiziano; Belgiorno, Vincenzo; et al. (Membranes (Basel), 2022)
Using an environmentally friendly approach for eliminating methylene blue from an aqueous solution, the authors developed a unique electrospun nanofiber membrane made of a combination of polyethersulfone and hydroxypropyl cellulose (PES/HPC). SEM results confirmed the formation of a uniformly sized nanofiber membrane with an ultrathin diameter of 168.5 nm (for PES/HPC) and 261.5 nm (for pristine PES), which can be correlated by observing the absorption peaks in FTIR spectra and their amorphous/crystalline phases in the XRD pattern. Additionally, TGA analysis indicated that the addition of HPC plays a role in modulating their thermal stability. Moreover, the blended nanofiber membrane exhibited better mechanical strength and good hydrophilicity (measured by the contact angle). The highest adsorption capacity was achieved at a neutral pH under room temperature (259.74 mg/g), and the pseudo-second-order model was found to be accurate. In accordance with the Langmuir fitted model and MB adsorption data, it was revealed that the adsorption process occurred in a monolayer form on the membrane surface. The adsorption capacity of the MB was affected by the presence of various concentrations of NaCl (0.1–0.5 M). The satisfactory reusability of the PES/HPC nanofiber membrane was revealed for up to five cycles. According to the mechanism given for the adsorption process, the electrostatic attraction was shown to be the most dominant in increasing the adsorption capacity. Based on these findings, it can be concluded that this unique membrane may be used for wastewater treatment operations with high efficiency and performance.